Does Type 1 Diabetes Mellitus Patients' Bone Mineral Density Differ From Healthy Controls'? - Original Investigation - Esma Demirhan; Esma Öcal Eriman; Afitap İçağasıoğlu; Sema Haliloğlu (Galenos Yayinevi, 2007)
Aim: To compare the tibia and radius bone mineral density (BMD) and speed of sound (SOS) measures of type 1 DM patients and healthy controls by using Quantitative ultrasonography (QUS) (Sunlight Omnisense 7000S/8000S). Patients and Methods: 40 type 1 DM (17 men, 23 women) and 26 healthy controls (20 women, 6 men),ranging in age from 30 to 50 years, were included in the study. Tibia and radius BMD of all the participants were measured by QUS. Weight and height were noted and BMI (body mass index) were calculated. DM duration, fracture story, nutrition habit and exercise story were also evaluated. Results: Mean age of type 1 DM group and control group were 36.8±5; 40.19±6.31 years respectively. Mean disease duration of type 1 DM group was: 12.4±6.63 years. Tibia T scores of type 1 DM group and control group were: 0.1±1.01; -0.4±1.37 (p=0.089) and radius T scores were -0.12±0.05; 0.05±1.17 (p=0.518) respectively. Tibia SOS values of type 1 DM group and control group were 3977.2±122.06; 3758.46±777.02 (p=0.084) and radius SOS values were 4124.7±110.23; 4163.31±119.98 (p=0.184) respectively. Conclusion: There was no significant difference between type 1 DM patients and healthy group's tibia and radius T scores and SOS values. Ostepenia was not detected in both groups. (From the World of Osteoporosis 2007;13:28-32)